2018
DOI: 10.3389/fpsyg.2018.00371
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lower Spiritual Well-Being, Social Support, Self-Esteem, Subjective Well-Being, Optimism and Hope Scores With Mild Cognitive Impairment and Mild Dementia

Abstract: Introduction: Positive psychology (PP) constructs contribute significantly to a better quality of life for people with various diseases. There are still few studies that have evaluated the evolution of these aspects during the progression of dementia.Objective: To compare the scores for self-esteem, life satisfaction, affect, spirituality, hope, optimism and perceived support network between elderly people with mild cognitive impairment (MCI), mild dementia and moderate dementia and control group.Methods: Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 81 publications
2
54
1
4
Order By: Relevance
“…One study demonstrated that individuals with MCI and mild dementia had lower spiritual well-being, social support, self-esteem, life satisfaction, positive affect, optimism, and hope, as well as higher negative affect scores, compared to a control group of healthy old-age people. 72 Similarly, another study reported that self-efficacy, optimism, and self-esteem were positively associated with living well (quality of life, well-being, and life satisfaction) among people with mild-tomoderate dementia from a community cohort. 73 Accordingly, other cross-sectional studies in people with dementia have revealed that higher self-esteem predicts higher quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…One study demonstrated that individuals with MCI and mild dementia had lower spiritual well-being, social support, self-esteem, life satisfaction, positive affect, optimism, and hope, as well as higher negative affect scores, compared to a control group of healthy old-age people. 72 Similarly, another study reported that self-efficacy, optimism, and self-esteem were positively associated with living well (quality of life, well-being, and life satisfaction) among people with mild-tomoderate dementia from a community cohort. 73 Accordingly, other cross-sectional studies in people with dementia have revealed that higher self-esteem predicts higher quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…This may lead to early evaluation and intervention, which contribute to a better cognitive outcome. However, it is plausible that cognitive impairments would have reciprocal relationships with the quality of life, subjective wellbeing, and functional disability in the elderly 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Even in these circumstances, support was provided to enable people with this level of disability to start and continue daily tasks themselves by making changes to daily necessities to support cognitive impairment, ascertaining the person's toileting rhythms and eating rhythms and enabling them to enjoy the experience of deliciousness and warmth when starting daily tasks, rather than simply assisting their action for each stage of the process. The self‐esteem of people with dementia tends to be adversely affected when ADL become difficult due to the effect of cognitive impairment (Dos Santos, Rocha, Fernandez, de Padua, & Reppold, ; Suwa, Otani, Tsujimura, Nogawa, & Shiya, ). However, care using not only the first factor, “Explain the process in the order of each individual action: explain the order of actions that comprise one activity of daily life and specifically show those actions,” but also the second factor, “Prevent non‐starts and interruptions: devise techniques in advance to ensure activities of daily life are not non‐started or interrupted,” enables the person to execute ADL, which may also maintain or improve their self‐esteem.…”
Section: Discussionmentioning
confidence: 99%
“…The self-esteem of people with dementia tends to be adversely affected when ADL become difficult due to the effect of cognitive impairment(Dos Santos, Rocha, Fernandez, de Padua, & Reppold, 2018;Suwa, Otani, Tsujimura, Nogawa, & Shiya, 2018).…”
mentioning
confidence: 99%